Mutually Engaging Encounter with the Use of Technology (MEET) between grandparents and grandchild an explanatory framework on closeness as a family outcome - Gonzalez, Armel B. (Manila College of Nursing, University of the Philippines Manila, 2022)
Technology and stress are part of our daily lives. With the challenges we face every day, people can easily get isolated and unstable. This study aims to provide an explanatory framework on closeness as a family outcome from the mutually engaging encounter with the use of technology (MEET) between a grandparent and a grandchild.

A sequential-independent mixed method design based on the timing dimension is used for the study. Survey, interview and video recordings are used as instruments for the quantitative data. Critical incident technique is used for the qualitative data using selective coding. Sample size is 109 dyads of grandparent and grandchild, 5 dyads agreed for in depth-interview for the CIT. Consents are obtained. Purposive and snowball techniques are used for sampling. The data gathering procedure is done remotely within 3-6 months among Filipino grandparents who raised their grandchildren in Manila, Philippines.

The result of the study reveals that the factors affecting the mutually engaging encounter with the use of technology are married grandparents, the grandchild’s very proficient use in technology and cellphone as the gadget used by the grandparents. However, only the environment factor shows statistical evidence (p= 0.065 at 90% level of significance) that shows that gadgets, specifically cellphone, used by the grandparents affects closeness, which stresses the role played by technology in mutually engaging encounters. Quantitative analysis also revealed that there is a very high degree of closeness between the grandparents and grandchild as a result of the MEET itself with significant p value of 0.056 at 90% level of significance. Qualitative analysis also supported the same finding by the many accounts by both the grandchildren and the grandparents in the critical incident technique.

Findings also show that adapting to situational changes, improving technological competence, enhancing family relations, and nurturing personal bond with grandparent/grandchild are distinct that emerged from their mutually engaging encounter with the use of technology (MEET). The assumptions of the study prove to be consistent with the result of the study that mutually engaging encounters give purpose and meaning to human-to-human interactions even while using technology that can lead to stability and wellness as evidenced by the high degree of closeness between the grandparents and grandchildren. Results show the MEET is optimized when grandchildren help grandparents navigate technology to enhance their competence and confidence. On the other hand, grandparents share with the grandchild insights and values regarding their own experiences while interacting with their grandchildren. It is concluded therefore that the findings of this study have provided an explanatory framework on the mutually engaging encounter with the use of technology (MEET) between the grandparents and grandchild leading to closeness as a family outcome.

MEET should be fostered among family members to promote bonding and improve family relations to increase likelihood of enhanced family processes. MEET should also be promoted in the health care setting between patients and health care workers to increase patient participation in plan of care and facilitate therapeutic nurse-patient relations. Since MEET is new concept, it can be explored and improved through further studies in the future. It is also highly recommended that a follow-up study be conducted in a different setting within the Filipino cultural perspective.
Dissertation (Doctor of Philosophy in Nursing) -- University of the Philippines Manila, December 2022.
Bibliography: leaves 142-156.
Keywords: Grandparents and grandchild -- Technology